Simulation of office’s operative temperature using ECOTECT model - Abdullah, Abd Halid; Abu Bakar, Siti Khatijah; Abd Rahman, Ismail (ZW Publisher, 2013)
Operative temperature (OT) is the significant evaluation criterion for occupant’s thermal comfort since it integrates dry bulb temperature (DBT) and mean radiant temperature (MRT) with their respective heat transfer coefficients weightage. This paper presents the comparison of simulated OT with the measured value of a selected office building. Field measurement was conducted on a two-storey office building in the Universiti Tun Hussein Onn Malaysia (UTHM) campus. Then, the office building is modelled using Ecotect Thermal Analysis software. Simulation on the model was carried out to generate its OT and this value was compared with the measured value. It has been found that Ecotect program can be reasonably used in simulating OT as the mean discrepancies between both predicted and measured values are 1.6% for ground floor and 5% for first floor of the office because it is less then threshold value of 10% as agreed by most researchers.